Examining Indonesian Accountants’ Dark Triad, Subjective Norm, and Peers’ Behavior in Influencing Their Ethical Intention - Norhamida, Hana; Tantri, Sakina; Suryani, Pesi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
Among the unpleasant human traits that have been introduced by researchers in the psychology literature is the Dark Triad. The Dark Triad are three characteristics that correlate with each other and attract attention in the empirical realm, namely Machiavellianism, Psychopathy and Narcissism (Machiavellianism, Psychopathy, and Narcissism). This study examines the ethical model of accountants in Indonesia. This study aims to investigate the effect of dark triad (which consists of Machiavellianism, narcissism, and psychopathy) and subjective norm toward perceived peers’ behavior and ethical intention. The method used in this study is quantitative method with survey as the data collection method. Using questionnaire, the data of this study were collected from 68 participants. This study used moderated regression analysis to analyze the data. The findings of this study indicate that dark triad does not significantly affect perceived peers’ behavior but significantly affects unethical intention. Meanwhile, subjective norm has a significant effect on perceived peers’ behavior but does not significantly affect unethical intention. This study also reveals that perceived peers’ behavior has a significant influence on unethical intention. This research provides benefits as literature contributor that describes the profile of Indonesian accountants according to personality theory and subjective norms, as well as how personality and subjective norms can shape characters that affect perceptions of unethical behavior, intentions to take unethical actions in decision making.